ANALISIS POTENSI PLTB DI PANTAI LOSARI MAKASSAR MENGGUNAKAN HOMER - Usman, Feliks Syahputra; Setiawan, Johan (CV SWA Anugerah, 2024)
This research analyzes the potential of the Bayu Power Plant (PLTB) on Losari Beach, Makassar, with the aim of exploring the use of renewable energy sources in Indonesia. Considering the increasing need for electrical energy and dependence on fossil fuels, the development of PLTB is a strategic solution to meet energy needs in a sustainable manner. In this study, HOMER (Hybrid Optimization of Multiple Energy Resources) software is used to simulate various power generation system configurations that combine wind turbines and solar panels. Wind speed and solar radiation data are obtained from trusted sources, such as NASA, to obtain accurate estimates of energy production. This research also considers economic analysis through Net Present Cost (NPC) and Cost of Energy (COE), as well as optimistic and pessimistic scenarios to assess project feasibility. It is hoped that the research results can make a significant contribution to the development of renewable energy in Indonesia's coastal areas, as well as increase public awareness about the importance of transitioning towards cleaner and more sustainable energy sources. Penelitian ini menganalisis potensi Pembangkit Listrik Tenaga Bayu (PLTB) di Pantai Losari, Makassar, dengan tujuan untuk mengeksplorasi pemanfaatan sumber energi terbarukan di Indonesia. Mengingat meningkatnya kebutuhan energi listrik dan ketergantungan pada bahan bakar fosil, pengembangan PLTB menjadi solusi strategis untuk memenuhi kebutuhan energi secara berkelanjutan. Dalam studi ini, perangkat lunak HOMER (Hybrid Optimization of Multiple Energy Resources) digunakan untuk mensimulasikan berbagai konfigurasi sistem pembangkit listrik yang menggabungkan turbin angin dan panel surya. Data kecepatan angin dan radiasi matahari diperoleh dari sumber terpercaya, seperti NASA, untuk mendapatkan estimasi produksi energi yang akurat. Penelitian ini juga mempertimbangkan analisis ekonomi melalui Net Present Cost (NPC) dan Cost of Energy (COE), serta skenario optimis dan pesimis untuk menilai kelayakan proyek. Hasil penelitian diharapkan dapat memberikan kontribusi signifikan terhadap pengembangan energi terbarukan di wilayah pesisir Indonesia, sekaligus meningkatkan kesadaran masyarakat tentang pentingnya transisi menuju sumber energi yang lebih bersih dan berkelanjutan.